SKAIMKU: A Learning Application for Word Structure and Affixation Based on Kudus Local Wisdom for Third Grade Elementary School Students (Feasibility and Practicality Study) - Dina Novitasari; Dwi Sari Fatul Amalia; Maulida Alif Nurul Zamzami; Rani Setiawaty (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to develop, test the feasibility and practicality of the SKAIMKU application (Word structure and affixes by linking Kudus local wisdom) as an innovative digital learning media to improve simple sentence writing skills of third grade elementary school students. Research Methods: The method sed is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The application was developed by integrating the Canva, Heyzine, and AppGeyser platforms, and contains Kudus local wisdom. The feasibility test was carried out by media experts and material experts, while the practicality test was measured through teacher and student responses. Finding/Results: The validation results showed that SKAIMKU was declared very feasible with an average score of 92.8% from media experts and from material experts. The results of the practicality test were also in the very practical category with a score of 89% from teachers and 96.2% from students. This application was considered interesting, easy to use, and relevant to the local cultural context of Kudus. Novelty: This research focuses on the integration of Kudus' local wisdom (such as Kudus's fame as a city of Islamic boarding school students (santri) and a city of kretek (cigarettes)) into a simple sentence-writing learning medium based on an Android educational game, specifically designed for third-grade elementary school students in Phase B.